Pengaruh Kepemimpinan Transformasional dan Motivasi Ekastrinsik Terhadap Kinerjakaryawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Dafatan Anugerah Abadi Serang Banten - Darari, Darari; Lutfi, Lutfi (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2019)
The research is meant to analyze the effect of transformational and work motivation on the intervening variable (research at PT Dafatan Anugrah Abadi, Serang – Banten). The respondents of this study touched 98 employees. Sampling method used is saturated sample, where the number of samples is equal to the number of population is 98 people. In this research the sampling technique is stratified sampling. Data collection using questionnaires and data analysis performed by using multiple linear regression analysis. The results show that transformational leadership has an improper relationship to the employee's performance, which is indicated by using the Inderect Effect of the coefficient value of -0.035 with a t value of 0.284. The value is smaller than t table 1.960. Extrinsic motivation has positive and significant correlation to employee performance, credit result on Influence Inderect show no direct variable of Extrinsic Motivation (ME) with Employee Performance (KP) through Job Satisfaction (KK) shows coefficient value of 0,368 with value of t amounted to 2.931. The value is greater than t table 1.960